Addiction to multiple oncogenes can be exploited to prevent the emergence of therapeutic resistance - Choi, Peter S. (National Academy of Sciences, 2014)
Many cancers exhibit sensitivity to the inhibition of a single genetic lesion, a property that has been successfully exploited with oncogene-targeted therapeutics. However, inhibition of single oncogenes often fails to result in sustained tumor regression due to the emergence of therapy-resistant cells. Here, we report that MYC-driven lymphomas frequently acquire activating mutations in β-catenin, including a previously unreported mutation in a splice acceptor site. Tumors with these genetic lesions are highly dependent on β-catenin for their survival and the suppression of β-catenin resulted in marked apoptosis causally related to a decrease in Bcl-xL expression. Using a novel inducible inhibitor of β-catenin, we illustrate that, although MYC withdrawal or β-catenin inhibition alone results in initial tumor regression, most tumors ultimately recurred, mimicking the clinical response to single-agent targeted therapy. Importantly, the simultaneous combined inhibition of both MYC and β-catenin promoted more rapid tumor regression and successfully prevented tumor recurrence. Hence, we demonstrated that MYC-induced tumors are addicted to mutant β-catenin, and the combined inactivation of MYC and β-catenin induces sustained tumor regression. Our results provide a proof of principle that targeting multiple oncogene addicted pathways can prevent therapeutic resistance.